Synthesis of graphene sand composite by using arenga palm and table sugar to remove methylene blue and nickel from aqueous solution - Norul Wahida, Kamaruzaman (2019)
Pollution of water sources has increased in a number of regions of the world due to the growth of industries and its untreated effluent discharge, increasing urbanization and energy intensive life styles, loss of forest cover, lack of environmental awareness and lack of implementation of environmental rules and regulations. The aim of the thesis is to synthesis green graphene sand composite (GSC) by using arenga palm sugar and table sugar as carbon sources to remove methylene blue and nickel from aqueous solution through adsorption process. The arenga palm sugar was chosen as carbon source due to the similarity on properties with ordinary table sugar and no research has been conducted so far on this particular material. The synthesis was conducted by removing deleterious materials on sand’s surfaces before sieved. The solutions of sugar were prepared and heated to 95 oC for 2 hours with constant stirring together with sand before being put in furnace with nitrogen environment to produce graphene sand composite, GSCaps and GSCts. The composites then were activated by using concentrated sulphuric acid to maximise the capacity of absorbency. The analyses on the characteristic of both GSC were conducted through field emission scanning electron microscope (FESEM), elemental dispersive x-ray (EDX), elemental mapping (EM) and raman spectroscopy. Field Emission Scanning Electron Microscope (FESEM) analyses exhibited that the sugar coating process was done uniformly as there were layers of coating sheets formation outside the sand particles’ surface. It was found that the biggest elements in the composite were carbon, oxygen and silica in scattered distribution. There was also a strong diffraction peak located at 26.66 ° and 26.80 ° which indicates the formation of the crystalline of the GSCaps and GSCts respectively which give glowing effect to the composites due to the light reflection. The test on raman spectroscopy detected two important peaks namely G and D band at 1547 cm-1 and 1292 cm-1 respectively. Adsorption test showed that 100 % of 1 ppm methylene blue and nickel were successfully adsorbed by using 1 g of GSC with 50 % and 48% adsorption in the first hour of contact respectively. Complete adsorption of methylene blue and nickel was successfully achieved at 10 – 12 hours of contact. The analysis exhibited pseudo second order equation is more appropriate in describing kinetic of the methylene blue and nickel adsorption with R2=0.9993 and R2=0.9972 by using GSCaps whereas R2=0.9981 and R2=0.9948 by using GSCts respectively. The isotherm data of methylene blue and nickel removal were fitted Langmuir model best with R2=0.9999 and R2=0.9975 by using GSCaps whereas R2=0.9945 and R2=0.9962 by using GSCts respectively. The reusability of GSCaps and GSCts recorded 87 % and 88 % adsorbency capacity loss before regeneration and able to restore approximately 76 % capacity in adsorbing methylene blue and nickel. In conclusion, both GSCs have shown potentials to be acted as good adsorbent with a total of 7 % adsorption increment comparing to conventional method, by using similar parameters setting in the experiment.